Sclerosperma and Podococcus in Gabon - Valkenburg, J. van; Sunderland, Terry C.H.; Banak, L.N.; Issembe, Y. (2007)
This paper focuses on some supposedly well known understory palms Sclerosperma and Podococcus. However, upon closer examination, the forest of Gabon once again reveals two botanical treasures, Sclerosperma walkeri and Podococcus acaulis, that had remained hidden in some long forgotten French periodicals.